Efektivitas Model Game Based Learning Menggunakan Aplikasi Blooket dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Bahasa Inggris Kelas VII di SMP Negeri 2 Cikijing - Widiantika, Wafa; Haerudin, Dodi Ahmad (Indo-MathEdu Intellectuals Journal, 2025)
The background of this research is the low learning outcomes of students due to the dominance of lecture methods and the lack of utilization of technology-based learning media. This study aims to determine the effectiveness of the Game Based Learning model assisted by the Blooket application in improving the learning outcomes of seventh-grade students in English subjects at SMP Negeri 2 Cikijing. This research employs a quantitative approach with a quasi-experimental method and an Nonequivalent Control Group Design. The sample consists of two classes: an experimental class that uses the Game Based Learning model assisted by the Blooket application, and a control class that uses conventional methods. Data collection techniques were carried out through pretests and posttests, which were then analyzed using normality tests, homogeneity tests, and t-tests (Independent Sample T-Test). The results of the hypothesis test show that the significance value (Sig. 2-tailed) is 0.000 < 0.05, indicating a significant difference in learning outcomes between the two classes. Therefore, the use of the Game Based Learning model supported by the Blooket application is proven to be effective in enhancing students’ learning outcomes. This model successfully creates an engaging and interactive learning environment that fosters student motivation and active participation in English learning.